Nutraceuticals production and bioactive properties of Leucopaxillus giganteus mycelium in the presence of different nitrogen sources - Barros, Lillian (2007)
Mushrooms have become attractive as a functional food and as source for the development of drugs and nutraceuticals [1-4]. In addition to dried mushrooms, alternative or substitute mushroom products are mycelia that could also be used as food and food-flavouring material, or in the formulation of nutraceuticals and functional foods. The add-value arising from mushrooms/mycelia bioactive properties can leave to an increase in its consumption and therefore stimulating the commercialisation of local edible species and the in vitro production of mycelium muslu·oom ( eg. For pharmaceutical industry)[5]. Leucopaxillus giganteus (Sowerby) Singer is a common Portuguese edible mushroom and belongs to the phyla Basidiomycete, order Agaricales, and family Tricholomataceae. This specie is used in chemical industry for extraction of clitocybin antibiotic. At present, between 80 and 85% of all medicinal mushroom products are obtained from the fruiting bodies, which have been either commercially farmed or collected from the wild. Only 15% of all products are based on extracts from mycelia L6]. In spite of a great need for useful bioactive metabolites production by submerged cultivation of mushrooms, the bioprocess development is still far from being thoroughly studied [7]. Usually, culture medium is important to the yield of any cultivation products and nitrogen source generally plays a significant role, as it is essential for cell proliferation and metabolite biosynthesis. Despite other studies carried out on the effect of nitrogen source on growth of edible mushrooms, no studies are known in Portuguese species and no reports are known about the influence of the nitrogen source in the bioactive properties of wild edible mushrooms.